2-(2,2-Dimethyl-2,3-dihydro-1-benzofuran-7-yloxy)acetic acid monohydrate - Yang, Lin-Tao (International Union of Crystallography, 2010)
In the title compound, C(12)H(14)O(4)·H(2)O, the dihydrobenzofuran ring adopts an envelope conformation with the substituted C atom 0.142 (1) Å out of the least-squares plane. In the crystal, the components are linked via intermolecular O(water)—H⋯O and O—H⋯O(water) hydrogen-bonding interactions, forming a three-dimensional network.